Arsenic and smokeless tobacco induce genotoxicity, sperm abnormality as well as oxidative stress in mice in vivo. (December 2016) - Das, Samrat; Upadhaya, Puja; Giri, Sarbani
Abstract Background Arsenic, a naturally occurring metalloid is a well-known water contaminant which causes a wide range of serious adverse health effects including cancer upon long-term exposure. Recent studies have shown high arsenic contamination in the ground water of North Eastern states of India including Southern Assam. Smokeless tobacco consumption locally known as "sadagura " is one of the most prevalent life style habit in southern Assam. The present study was undertaken in mice test systemin vivo . Mice were exposed to smokeless tobacco (5 mg/kg body weight /day) and sodium arsenite (0.2 mg/kg body weight /day, 2 mg/kg body weight/day) independently and in combination for 90 days. Results The results were compared with groups with only sodium arsenite exposure and groups which were exposed to only smokeless tobacco extract. Genotoxicity was evaluated by studying the incidence of micronucleated polychromatic erythrocytes from bone marrow. Both the tested doses of sodium arsenite induced statistically significant micronucleated polychromatic erythrocytes as compared to control group, however, sodium arsenite and smokeless tobacco extract could not increase the incidence of micronucleated polychromatic erythrocytes as compared to their individual counterparts when treated in combination in mice test system. Germ cell toxicity was evaluated by recording the sperm head abnormalities and total sperm count. Combined treatment of sodium arsenite and smokeless tobacco extract in lower dose induced a significant increase in sperm head abnormality as compared to only sodium arsenite and smokeless tobacco extract. Liver, kidney and intestine tissues were analyzed for various oxidative stress evaluations such as lipid peroxidation (MDA), Glutathione (GSH) and superoxide dismutase (SOD) assay. Sodium arsenite in combination with smokeless tobacco extract show higher genotoxic and germ cell toxic effects as compared to control but not when compared to their individual counterparts. Conclusion Impairment of the sperm head morphology by sodium arsenite and smokeless tobacco extract alone and in combination with lower dose of sodium arsenite could be oxidative stress mediated effects. Besides, combination treatment of both the agents may not produce additive effects related to micronucleated polychromatic erythrocytes induction and decline of total sperm count.